2011
DOI: 10.3892/ijo.2010.892
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin modulates the adhesion and growth of hepatocellular carcinoma cells via decrease of integrin expression and ROCK

Abstract: Abstract. Hepatocellular carcinoma (HCC) has become a global health concern and is one of the leading causes of cancer death after lung and gastric cancers. It has been suggested that the 3-hydroxy-3-methyl-glutarylcoenzymeCoA (HMG-CoA) reductase inhibitor simvastatin exhibits anticancer properties. To this end, we analyzed the influence of simvastatin on the cell growth and adhesion of HCC and evaluated the yet poorly characterized mechanism of action of simvastatin in HCC. HepG2 and Huh7 cells were treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…In addition, our results showed that simvastatin decreased CCL17-induced HT-29 cell migration without any concomitant effects on cell proliferation of apoptosis, indicating a direct effect of simvastatin on colon cancer cell migration, which might be of beneficial value. Although this is the first report to show that simvastatin inhibits colon cancer cell migration in response to chemokine signaling, other investigations 11 have found that simvastatin can inhibit migration of breast [21], hepatic [22], renal [17] and prostate [23] cancer cells, supporting the concept that simvastatin is an effective inhibitor of tumor cell migration.…”
Section: Role Of Hmg-coa Reductase and Geranygeranylation In Cell Migsupporting
confidence: 58%
“…In addition, our results showed that simvastatin decreased CCL17-induced HT-29 cell migration without any concomitant effects on cell proliferation of apoptosis, indicating a direct effect of simvastatin on colon cancer cell migration, which might be of beneficial value. Although this is the first report to show that simvastatin inhibits colon cancer cell migration in response to chemokine signaling, other investigations 11 have found that simvastatin can inhibit migration of breast [21], hepatic [22], renal [17] and prostate [23] cancer cells, supporting the concept that simvastatin is an effective inhibitor of tumor cell migration.…”
Section: Role Of Hmg-coa Reductase and Geranygeranylation In Cell Migsupporting
confidence: 58%
“…The potential anti-carcinogenic effects of simvastatin alone or in combination with various anticancer therapies have been documented in a number of tumor cell lines and mouse models, including colorectal [10], hepatocellular [11], prostate [12], breast [13], and hematological malignancies [14]. How simvastatin exerts its anticancer effects is not fully understood, but it has been found to modulate various signaling cascades including mitogen-activated protein kinases [15,16], PI3-K/ Akt [17], NF-κB [18][19][20], STAT3 [14], cell cycle-dependent kinases [21], Rho-dependent kinase [22,23], and Ras-related C3 botulinum toxin substrate 1 [24].…”
mentioning
confidence: 99%
“…Another study showed, using the same cell lines, that simvastatin induced apoptosis, G0/G1 cell cycle arrest, suppressed CDKs and up--regulated p19 and p27 [71]. The authors further showed that simvastatin suppressed cell adhesion, paralleled by a decrease of B1, B2 and A3 integrins and a strong suppression of ROCK--I in these cell lines [71]. Treatment of Huh--7 HCC cells by lovastatin induced apoptosis, an effect that was further amplified by enzastaurin, a PKC--β inhibitor, in a strategy developed to counteract the inductive effect of lovastatin on this enzyme [72].…”
Section: 23--liver Cancermentioning
confidence: 95%
“…In addition, co--treatments of HepG2 cells with EPA and lovastatin, two separate classes of HMG--CoA reductase inhibitors, amplified cell growth arrest, as compared to lovastatin alone [70]. Another study showed, using the same cell lines, that simvastatin induced apoptosis, G0/G1 cell cycle arrest, suppressed CDKs and up--regulated p19 and p27 [71]. The authors further showed that simvastatin suppressed cell adhesion, paralleled by a decrease of B1, B2 and A3 integrins and a strong suppression of ROCK--I in these cell lines [71].…”
Section: 23--liver Cancermentioning
confidence: 99%